Delocalized Electrons via In Situ CNT Growth on Au/g‐C3N4 for Boosting Photocatalytic H2 Evolution. (28th June 2022) - Xia, Zhihua; Chen, Cheng; Qi, Xiaoying; Xu, Quanlong; Tang, Hua; Liu, Gang
Abstract: Graphitic carbon nitride (g‐C3 N4 ) is a prominent polymer photocatalyst, yet it suffers from severe charge carrier recombination in photocatalysis. Herein, carbon nanotubes (CNTs) are in situ grown onto g‐C3 N4 nanosheets via a chemical vapor deposition (CVD) process, catalyzed by Au nanoparticles (NPs) pre‐deposited on g‐C3 N4 surface via deposition‐precipitation. Systematic characterizations, in particular femtosecond transient absorption spectroscopy (fs‐TAS) and time‐resolved photoluminescence (TR‐PL), prove that CNTs can efficiently extract the localized electrons in the tri‐s‐triazine units of g‐C3 N4, thereby enhancing charge carrier diffusion and separation. As a result, CNT/Au/g‐C3 N4 nanocomposites display a H2 evolution rate of 0.95 mmol g −1 h −1, which is about three times higher than that of Au/g‐C3 N4 . This work may pave a path to explore the full potential of CNTs to modify g‐C3 N4 or other photocatalysts in solar‐to‐chemical energy conversion. Abstract : Carbon nanotubes in situ grown on Au/g‐C3 N4 by chemical vapor deposition open a new electron transfer channel and greatly improve photo‐excited charge‐carrier transfer and separation, thereby promoting photocatalytic H2 generation performance.